A Dean-flow-coupled interfacial viscoelastic fluid for microparticle separation applied in a cell smear method. Issue 20 (4th September 2019) - Shi, Xin; Liu, Liyan; Cao, Wenfeng; Zhu, Guorui; Tan, Wei
Abstract : An interfacial microfluidic device realizing cell separation and washing simultaneously and efficiently. Abstract : We propose a novel microfluidic device for continuous, label-free and size-selective particle separation. The process consists of two stages: the particle separation based on the pre-focus of sheath flow and the size-selective interface between a Newtonian sample fluid and non-Newtonian poly(ethylene oxide) (PEO) solution (1st stage), and separation distance expansion due to the contraction–expansion structure (2nd stage). The force balance has been analyzed to explore the mechanism and the factors in the particle migration. In the 1st stage, the inertial lift force and the interfacial elastic lift force are a couple of counter forces which only allow the target particles to penetrate the interface. By controlling the flow rate ratio and the PEO concentration, all unwanted particles can be confined to the sample layer. In the 2nd stage, the elastic lift force is used to counteract the inertial lift force, which increases the predomination of the Dean drag force in the lateral migration of the target particles. We conclude that the separation distance is not monotonically increasing with the elastic lift force but peaks at 50–150 ppm. Thus, an optimal parameter for particle separation in our device is obtained. Compared to a similar method without the 2nd stage and the same device without the 1st stage, the distance between the target particles and the unwanted particles could increase by approximately 35.8% and 101.2%, respectively. Finally, a sensitive, time saving and no background-interfering cell smear method is approved to diagnose the malignant pleural effusion efficiently.